Healthy Meal Plans - Linda B. Bobroff (EDIS)
A meal plan is a guide to help you plan daily meals and snacks. It allows you to eat foods you enjoy and that provide a good balance of nutrients for your health. Meal plans can be used by anyone interested in healthy eating. They are very helpful for people who want to manage their weight. This 20-page fact sheet was written by Linda B. Bobroff and published by the UF Department of Family, Youth and Community Sciences, October 2012.